Redescription of four species of Hatschekia (Copepoda: Siphonostomatoida: Hatschekiidae) parasitic on tetraodontiform fishes from Japan - Uyeno, Daisuke; Nagasawa, Kazuya (Zootaxa, 2009)
Four species of the genus Hatschekia Poche, 1902 (Copepoda: Siphonostomatoida; Hatschekiidae) are redescribed based on specimens collected from tetraodontiform fishes captured recently in Japanese waters: female H. iridescens Wilson, 1913 from Diodon liturosus Shaw (representing a new host record), D. hystrix L., and D. holocanthus L.; female Hatschekia legouli Nuñes-Ruivo, 1954 (representing a new parasite record for Japan) from Chilomycterus reticulatus L.; female H. ostracii Yamaguti, 1953 from Ostracion immaculatus Temminck & Schlegel and O. cubicus L.; and both sexes of H. monacanthi Yamaguti, 1939 from Thamnaconus modestus (Günther). Proportions of various parts of the female body and appendages are included as important characters to distinguish morphologically similar species. A key to the 20 species of Hatschekia reported from Japanese waters is also included.